2020
DOI: 10.1186/s12935-020-01321-9
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG22 facilitates the malignant phenotypes in triple-negative breast cancer via sponging miR-324-3p and upregulating SUDS3

Abstract: Background: Increasing evidence has indicated the important role of long non-coding RNAs (lncRNAs) in regulating the development and progression of cancers, including triple-negative breast cancer (TNBC). Small nucleolar RNA host gene 22 (SNHG22) is a novel lncRNA that has been identified as tumor-contributor in ovarian carcinoma. However, its function has not been explored in TNBC. Methods: qRT-PCR was used to identify gene expression at mRNA level while western blot was utilized to analyze the protein level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
(21 reference statements)
2
16
0
Order By: Relevance
“… 29 In line with our results, SNHG22 was measured to be highly expressed in triple-negative breast cancer tissues by a prior investigation. 20 These findings indirectly supported our results of SNHG22 overexpression in GC tissues. Moreover, our data suggested that SNHG22 silencing restrained cell proliferation, migration, invasion, and angiogenesis but facilitated cell apoptosis and cell cycle arrest in GC.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… 29 In line with our results, SNHG22 was measured to be highly expressed in triple-negative breast cancer tissues by a prior investigation. 20 These findings indirectly supported our results of SNHG22 overexpression in GC tissues. Moreover, our data suggested that SNHG22 silencing restrained cell proliferation, migration, invasion, and angiogenesis but facilitated cell apoptosis and cell cycle arrest in GC.…”
Section: Discussionsupporting
confidence: 87%
“…SNHG22 has shown cancer-promoting effects in numerous cancers. 11 , 20 , 21 However, little is acknowledged about whether SNHG22 orchestrated GC. Therefore, we tested whether SNHG22 mediated GC development.…”
Section: Resultsmentioning
confidence: 99%
“…7 Next, Koduru et al 8 proposed that the level of SNHG22 could be served as a biomarker during the malignant transformation of hepatocellular carcinoma. Another, Fang et al 9 documented that SNHG22 regulated triple-negative breast cancer via the miR-324-3p/SUDS3 axis and provided a promising targeted therapy. Recently, SNHG22 acts as a ceRNA to regulate Gal-1 expression by competitively binding to miR-2467 in EOC.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can elicit biological functions by targeting and repressing their downstream messenger RNAs (mRNAs) 30 . Therefore, we sought to figure out the downstream targets of miR‐489‐3p.…”
Section: Resultsmentioning
confidence: 99%